The score - Oz, Frank; Salem, Kario; Dobbs, Lem; Smith, Scott Marshall; De Niro, Robert; Norton, Edward; Brando, Marlon; Shore, Howard; Horseshoe Bay Productions; Paramount Home Video (Firm) (Hollywood, Calif. : Paramount Home Video, 2001)
Aging thief pulls off one more heist at the urging of an upstart thief.
Originally released as a motion picture.
Features: interactive menus, scene selection, theatrical trailer, the making-of "The score," additional footage, and commentary by director Frank Oz and director of photography Rob Hahn.
Director of photography, Rob Hahn; production design, Jackson De Govia; editor, Richard Pearson; music, Howard Shore.
Robert DeNiro, Edward Norton, Marlon Brando, Angela Bassett.
MPAA rating: R.
DVD, Dolby digital 5.1, surround.
Keywords: Theft -- Drama; Video recordings for hard of hearing people; Feature films